Population pharmacokinetic models of anti-PD-1 mAbs in patients with multiple tumor types: A systematic review - Shang, Jingyuan; Huang, Lin; Huang, Jing; Ren, Xiaolei; Liu, Yi; Feng, Yufei (Frontiers in Immunology, 2022)
Aims and background A number of PPK models of anti-PD-1 mAbs in multiple tumor types have been published to characterize influencing factors of their pharmacokinetics. This review aimed to describe PPK models of anti-PD-1 mAbs, investigate the magnitude and types of covariate effect on PK parameters, provide reference for building PPK models of other anti-PD-1 mAbs and identify areas requiring additional research to facilitate the application of PPK models. Methods A systematic search for analyses about PPK models of eleven anti-PD-1 mAbs on the market that were carried out in humans was made using PubMed, EMBASE and the Cochrane Library. The search covered the period from the inception of the databases to April 2022. Results Currently, there are fourteen analyses about PPK models of anti-PD-1 mAbs summarized in this review, including seven models referred to nivolumab, four referred to pembrolizumab, one referred to cemiplimab, one referred to camrelizumab and one referred to dostarlimab. Most analyses described pharmacokinetics of anti-PD-1 mAbs by a two-compartment model with time-varying CL by a sigmoidal maximum effect. The estimated CL and volume of VC ranged from 0.179 to 0.290 L/day and 2.98 to 4.46 L, respectively. The median (range) of interindividual variability (IIV) for CL and VC was 30.9% (8.7-50.8%) and 29.0% (4.32-40.7%), respectively. The commonly identified significant covariates were body weight (BW) on CL and VC, and albumin (ALB), tumor type, sex, performance status (PS) on CL. Other less assessed significant covariates included lactate dehydrogenase (LDH), immunoglobulin G (IgG), ipilimumab coadministration (IPICO) on CL, and body mass index (BMI), mesothelioma (MESO) on VC. Conclusion This review provides detailed information about characteristics of anti-PD-1 mAbs’ PPK models, the effects of covariates on PK parameters, as well as the current status of models’ application. ALB, BW, specific tumor type, sex and PS should be considered for the future anti-PD-1 mAbs’ PPK model development. Other potential covariates assessed less frequently but still have significance (e.g., LDH, IgG and IPICO) should not be ignored. Thus, further research and thorough investigation are needed to assess new or potential covariates, which will pave the way for personalized anti-PD-1 mAbs therapy.